Analisis Kepuasan Pengguna Website Manajemen Informatika Dengan Metode EUCS Berbasis CMS - Yusuf Sutanto (INFORMATIKA, 2015)
This study reviews Satisfaction Analysis Website users with the methods EUCS Information Management Framework based CMS (Content Management System). Case Studies in the trial is progdi informatics management at AUB Surakarta. The purpose of this study was to determine how much of the expected value and the value of reality obtained (satisfaction) of the student or student to facilities / features of the website management informatics. Estimated value of the results of this analysis will be used as guidelines for courses in evaluating and developing the quality of education in D3-winning Information Management adi Bhirawa STIE Surakarta to become universities that excel in quality of education and teaching. In this case study, the research instrument that will be used is the End User Computing Satisfaction (EUCS) which means the satisfaction of users who use the software. In the method of analysis of satisfaction with EUCS approach, the variables used to measure satisfaction there are 5 dimensions to be studied to measure satisfaction, namely: Content, Format, Accuracy, Ease of Use, Save time. The test instrument used in this study using SEM methods, and data analysis are also using SEM. Data were used to analyze user satisfaction is a student information management that are still active, will pass and that has alumni. The results of the analysis of these variables to calculate how high student satisfaction and student of the website features information management.Keyword: CMS, eucs,  Informatics management.